A fruit in the hand or two in the bush? Divergent risk preferences in chimpanzees and bonobos - Heilbronner, Sarah R; Rosati, Alexandra G; Stevens, Jeffrey R; Hare, Brian; Hauser, Marc D (Biology letters (2005), 2008)
Human and non-human animals tend to avoid risky prospects. If such patterns of economic choice are adaptive, risk preferences should reflect the typical decision-making environments faced by organisms. However, this approach has not been widely used to examine the risk sensitivity in closely related species with different ecologies. Here, we experimentally examined risk-sensitive behaviour in chimpanzees (Pan troglodytes) and bonobos (Pan paniscus), closely related species whose distinct ecologies are thought to be the major selective force shaping their unique behavioural repertoires. Because chimpanzees exploit riskier food sources in the wild, we predicted that they would exhibit greater tolerance for risk in choices about food. Results confirmed this prediction: chimpanzees significantly preferred the risky option, whereas bonobos preferred the fixed option. These results provide a relatively rare example of risk-prone behaviour in the context of gains and show how ecological pressures can sculpt economic decision making.